1963
DOI: 10.1109/tap.1963.1138032
|View full text |Cite
|
Sign up to set email alerts
|

Very-low-frequency propagation below the bottom of the sea

Abstract: In the search for extremely reliable electromagnetic communication to submerged submarines, the question arose, * "What is the effect of the roughness and irregularity of the sea surface on the propagation of electromagnetic waves?" The purpose of this investigation is to obtain an engineering-understanding of the effect of the rough air-sea interface on electromagnetic signals used in communication to submerged submarines. The frequency of the electromagnetic wave is restricted to the3 ELF or VLF range. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1978
1978
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…The theory of propagation for ELF/SLF (<300 Hz) electromagnetic (EM) fields through, under and over the ocean from a submerged source has been investigated for more than fifty years as a means for communication, underwater detection and geophysical exploration (e.g. Mott & Biggs 1963; Bannister 1968; Chave et al 1990). Pioneering measurements by Cox et al (1978) showed that the natural background noise in the electric field at frequencies around 1 Hz is extremely low (∼1 pV m –1 ), suggesting that the weak fields induced within Earth by a near‐seafloor artificial source could be detected at large (many kilometres) source–receiver offsets.…”
Section: Introductionmentioning
confidence: 99%
“…The theory of propagation for ELF/SLF (<300 Hz) electromagnetic (EM) fields through, under and over the ocean from a submerged source has been investigated for more than fifty years as a means for communication, underwater detection and geophysical exploration (e.g. Mott & Biggs 1963; Bannister 1968; Chave et al 1990). Pioneering measurements by Cox et al (1978) showed that the natural background noise in the electric field at frequencies around 1 Hz is extremely low (∼1 pV m –1 ), suggesting that the weak fields induced within Earth by a near‐seafloor artificial source could be detected at large (many kilometres) source–receiver offsets.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 8 shows the comparison of the uniform field 30 kHz breakdown voltages obtained experimentally with those calculated using Equations (1) and (2) for the original and extrapolated gap Figure 8. Comparison of the experimental uniform field 30 kHz breakdown voltages to the estimates calculated using Equations (1) and (2). Breakdown voltages are plotted as a function of gap length.…”
Section: Model To Predict Breakdown Voltage For Uniform Field Gapsmentioning
confidence: 99%
“…This is because the earth and the D region of the ionosphere work as a waveguide at this frequency range [1]. VLF/LF signals penetrate seawater somewhat and can be used for communication to submerged objects at moderate depths [1,2]. The U.S. Navy operates 10 high-power VLF/LF transmitting stations for strategic purposes.…”
mentioning
confidence: 99%
“…The high-speed timer can ensure the time interval ΔT is shorter so as to have more time slots M in a fixed pulse cycle. Thus, the data bits transmitted by one pulse can be increased according to Equation (1), and higher data rate can be realized for PPM communication. In order to avoid the adverse effects by time slots overlapping, high-stability clock in the range of above 10 -8 is indispensable, too.…”
Section: Ppm Modulatormentioning
confidence: 99%
“…Nowadays, the normal means of underwater communicating is through VLF radio which sends encrypted wireless teletype. Since VLF electromagnetic radiation is attenuated rapidly by seawater, the submerged receiving antenna must be quite near the surface [1][2]. In order to realize greater depth contact, blue-laser communication was developed from the early 1960s.…”
Section: Introductionmentioning
confidence: 99%